MANGROVE EDUCATIONAL TOURISM DESIGN WITH SUSTAINABLE ARCHITECTURE APPROACH IN PANTAI KAMPUNG NIPAH, SERDANG BEDAGAI - Santika, Rifa Lisly; Ginting , Nurlisa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Mangrove educational tourism offers an in-depth understanding of the ecologically, economically, and socially valuable mangrove ecosystem. Indonesia, with the largest mangrove ecosystem in the world, faces the challenge of mangrove destruction due to irresponsible land conversion. Conservation efforts through educational tourism can improve the local economy and reduce carbon emissions. A sustainable approach to planning and development, involving the principles of eco-friendly architecture, is essential to protect and restore coastal ecosystems. The implementation of energy strategies, water and waste management, and cultural preservation in the design of tourism villages will ensure environmental sustainability and community well-being. Intensive environmental studies and education can raise global awareness of the importance of mangroves, support sustainable tourism, and contribute to greenhouse gas emission reduction targets.